Pengelolaan Manajemen Keuangan: Prioritas, Evaluasi Dan Akuntabilitas Di Sman 9 Bandung - Livia Anggina; Mirna Kurniati; Annisa Rizki Pebriani (Universitas Maritim AMNI Semarang, 2024)
This study aims to analyze financial management at SMAN 9 Bandung, focusing on efficiency, prioritization, and accountability. Using a qualitative approach, data were collected through structured interviews with the school treasurer to explore challenges, practices, and solutions in fund management. The findings reveal that the primary funding sources are BOS and BOP, which are often insufficient to meet operational needs. Budget preparation involves collaboration among the principal, teachers, and school committee, while financial oversight is enhanced through the ARKAS application to ensure transparency. Key challenges include limited funds and adjustments to new policy-driven needs. Diversifying funding sources, optimizing budgets, and empowering the school committee are recommended solutions to improve financial management and educational quality